Implementing And Designing a Vocabulary Study Program: English For Academic Purposes In An Ecuadorian University. - Moreira Cuadros, Loretta (2016)
The purpose of this study is to develop and implement a program for learning second language (L2) academic vocabulary with the objective of enhancing vocabulary learning strategies for reading proficiency and comprehension. This specially tailored program, based on language learning research, consists of five alternative strategies in order to identify ways of learning academic vocabulary for university level efl learners. Vocabulary knowledge not only implies being familiar with the meaning of a word, but also with its form (spoken, written, and its affixation) and its uses (collocations, grammatical pattern, and limits of its use). My experience as an english teacher of university students is that learners have considerable technical vocabulary because they are required to read texts in english related to their field of study. For that reason, their word knowledge is merely related to meaning by translation.